Selection of Optimal Functional Lymphatic Vessel Cutoff Size in Supermicrosurgical Lymphaticovenous Anastomosis in Lower Extremity Lymphedema. Issue 1 (23rd November 2021) - Yang, Johnson Chia-Shen; Wu, Shao-Chun; Hayashi, Akitatsu; Lin, Wei-Che; Wang, Yu-Ming; Luo, Sheng-Dean; Chiang, Min-Hsien; Hsieh, Ching-Hua
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Functional lymphatic vessels are essential for supermicrosurgical lymphaticovenous anastomosis. Theoretically, the larger the lymphatic vessel, the better the flow. However, large lymphatic vessels are not readily available. Since the introduction of lymphaticovenous anastomosis, no guidelines have been set as to how small a lymphatic vessel is still worthwhile for anastomosis. Methods: In this longitudinal cohort study, unilateral lower limb lymphedema patients who underwent lymphaticovenous anastomosis between March of 2016 and January of 2019 were included. Demographic data and intraoperative findings including the number and size of lymphatic vessels were recorded. The cutoff size was determined by receiver operating characteristic curve analysis, based on the functional properties of lymphatic vessels. Clinical correlation was made with post–lymphaticovenous anastomosis volume measured by magnetic resonance volumetry. Results: A total of 141 consecutive patients (124 women and 17 men) with a median age of 60.0 years (range, 56.7 to 61.2 years) were included. The cutoff size for a functional lymphatic vessel was determined to be 0.50 mm (i.e., lymphatic vessel 0.5 ) from a total of 1048 lymphatic vessels. Significant differences were found between the number of lymphatic vessels 0.5 anastomosed (zero to one, two to three, and greater than over equal to four lymphatic vessels 0.5 ), the median post–lymphaticovenous anastomosis volume reduction (in milliliters) ( p < 0.001), and the median percentage volume reduction ( p = 0.012). Conclusions: Lymphatic vessel 0.5 can be a valuable reference for lymphaticovenous anastomosis. Post–lymphaticovenous anastomosis outcome can be enhanced with the use of lymphatic vessel 0.5 for anastomoses. CLINICAL QUESTION/LEVEL OF EVIDENCE: Risk, II.